Government Policy in the Natural Resource Management of Local Community - Revency Vania Rugebregt; Abrar Saleng; Farida Patittingi (Hasanuddin Law Review, 2016)
Natural resource management is an important thing that should be done by the community for survival. Consciously of many ways in the management of natural resources has resulted in environmental damage, coupled with government policies that give permission without good supervision to entrepreneurs or private individuals in natural resource management adds a long list of environmental damage. In the last three decades, governments tend to ignore the phenomenon of legal pluralism in the legal development policy, preparation of legal instruments, as well as the implementation of the law through political neglect of the fact legal pluralism. So the product of legislation, especially those that set natural resource management, normatively ignore and displace the rights of indigenous peoples and local over control, management, and utilization of natural resources. Moreover, with deprivation of the rights of indigenous peoples’ customary rights and the implementation of development without taking into consideration the pattern of spatial planning, more and enlarge the conflict between the government and society.